PERAN KEPOLISIAN DALAM PENANGANAN UNJUK RASA (UU NO 2 TAHUN 2002 TENTANG KEPOLISIAN REPUBLIK INDONESIA) - Adhe Ismail Ananda; Muhammad Yusuf Natsir (IAI Al-Mawaddah Warrahmah Kolaka, 2020)
A rally or demonstration is a protest movement carried out by a group of people in public. However, demonstrations can also be interpreted as an activity to express opinions in public. Thus demonstration activities are actually a form of human right that is protected by law, in realizing the will of citizens in expressing opinions freely it must be maintained, so that the entire institutional social order is maintained from irregularities or violations of the law and can guarantee a sense of security in life. society, running smoothly, orderly and safely in accordance with what is the purpose of the demonstration. The police are law enforcement officers who directly deal with this matter, so this research examines the role and duties of the police in handling demonstrations in the title, Implementation of the duties and authorities of the Sabhara police unit in handling demonstrations in accordance with the Republic of Indonesia Police Law No. 2 of 2002 This study uses a sociological juridical approach, which is an approach that examines law and its systematics which is then applied to examine a problem in society with the aim of obtaining a fact, formulating a problem and finding the root of the problem. In dealing with demonstrations in this study, the police were at the forefront, namely at the stage of supervising the progress of demonstration activities, the duties of the Sabhara police in this supervision were directly related to the masses in the field, the police experienced only a few obstacles but could be handled properly